2006
DOI: 10.1590/s0100-69912006000300005
|View full text |Cite
|
Sign up to set email alerts
|

Operação do refluxo gastro-esofágico isolada ou associada à colecistectomia: avaliação do estresse cirúrgico pela dosagem hormonal e de citocinas

Abstract: RESUMO: Objetivo: O objetivo do presente estudo é comparar o estresse cirúrgico por meio de dosagens hormonais (ACTH e cortisol) e de citocinas (IL-4, IL-10, TNF-a, e IFN-g), em pacientes que foram submetidos somente à operação da transição esofagogástrica com aqueles submetidos à operação da transição esofagogástrica associada à colecistectomia. Método: Foram estudados 31 pacientes , sendo 19 submetidos à operação da transição esofagogástrica e 12, que apresentavam associação de colelitíase, foram submetidos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…Several studies have shown that videolaparoscopy (VLP) has a number of advantages in relation to laparotomy, such as: pain reduction and lower consumption of analgesics in the postoperative period, smaller skin incision, reduced bleeding, smaller need for hospitalization at Intensive Care Units, fewer infectious complications, lower pulmonary dysfunction, shorter hospitalization periods and, from the viewpoint of surgical stress, it shows less trauma, as measured by stress hormones (ACTH and cortisol) 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that videolaparoscopy (VLP) has a number of advantages in relation to laparotomy, such as: pain reduction and lower consumption of analgesics in the postoperative period, smaller skin incision, reduced bleeding, smaller need for hospitalization at Intensive Care Units, fewer infectious complications, lower pulmonary dysfunction, shorter hospitalization periods and, from the viewpoint of surgical stress, it shows less trauma, as measured by stress hormones (ACTH and cortisol) 2 .…”
Section: Introductionmentioning
confidence: 99%